3H-Imidazo[4, 5-b]pyridine-6-carboxylic acid derivatives as rexinoids with reduced teratogenicity. Issue 15 (1st August 2019) - Takamura, Yuta; Takahashi, Manami; Nishii, Midori; Shibahara, Osamu; Watanabe, Masaki; Fujihara, Michiko; Kakuta, Hiroki
Graphical abstract: Abstract: Several retinoid X receptor (RXR) ligands (rexinoids), such as bexarotene (1 ), exhibit teratogenicity, which is a serious impediment to their clinical application. We considered that rexinoids with a lower level of maximal RXR transcription activation (i.e., partial agonists) and lower lipid solubility might show weaker adverse side effects. Based on this idea, we modified our previously reported pentamethyltetralin-type RXR partial agonists 5 and 6 to reduce their lipophilicity. Here, we report a new RXR partial agonist, 3-(3, 5, 5, 8, 8-pentamethyl-5, 6, 7, 8-tetrahydronaphthalen-2-yl)-2-(trifluoromethyl)-3 H -imidazo[4, 5- b ]pyridine-6-carboxylic acid (8, CATF-PMN), which showed greatly reduced teratogenicity in zebrafish embryos.